2020
DOI: 10.1080/16549716.2020.1770967
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the INTERGROWTH-21 st gestational dating and fetal and newborn growth standards in Nairobi, Kenya: women’s experiences with ultrasound and newborn assessment

Abstract: Background: In order to make further gains in preventing newborn deaths, effective interventions are needed. Ultrasounds and newborn anthropometry are proven interventions to identify preterm birth complications, the leading cause of newborn deaths. The INTERGROWTH-21 st global gestational dating and fetal and newborn growth standards prescribe optimal growth in any population. Jacaranda Health in Kenya was the first lowresource health facility to implement the standards and evaluate their feasibility and acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A reliable expected date of delivery (EDD) is important for pregnant women in planning for a safe and uneventful delivery and critical for clinical management of obstetric emergencies [ 1 , 2 ]. In an implementation study of the Intergrowth-21 gestational dating in Kenya, all respondents interviewed reported that the EDD helped them to prepare for delivery financially and logistically [ 3 ]. According to the WHO guidelines pregnant women should have at least one ultrasound (US) before 24 weeks in pregnancy to determine the gestational age (GA), EDD and identify fetal anomalies and poor fetal growth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A reliable expected date of delivery (EDD) is important for pregnant women in planning for a safe and uneventful delivery and critical for clinical management of obstetric emergencies [ 1 , 2 ]. In an implementation study of the Intergrowth-21 gestational dating in Kenya, all respondents interviewed reported that the EDD helped them to prepare for delivery financially and logistically [ 3 ]. According to the WHO guidelines pregnant women should have at least one ultrasound (US) before 24 weeks in pregnancy to determine the gestational age (GA), EDD and identify fetal anomalies and poor fetal growth [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the WHO guidelines pregnant women should have at least one ultrasound (US) before 24 weeks in pregnancy to determine the gestational age (GA), EDD and identify fetal anomalies and poor fetal growth [ 4 ]. In low and middle income countries (LMIC) the availability of an ultrasound machine and ultrasound expertise are often limited to secondary and tertiary level facilities [ 3 – 6 ] and pregnant women attending primary health care clinics are referred to hospitals and Midwifery Outpatient Units for an US. However, long waiting times and financial constraints together with late antenatal attendance often delay an ultrasound examination to after 24 weeks of pregnancy [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finding out the fetal sex was important for respondents in a range of contexts, in terms of imaging their future baby, and practical planning [ 28 , 45 , 48 , 68 70 ]. However, in some circumstances, this knowledge had negative consequences [ 30 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…The scan appointment was a source of great excitement, joy and relief for many couples, providing a chance to bond with their baby, whilst also instilling a sense of responsibility, particularly amongst fathers and other co-parents [ 19 , 21 , 32 , 41 , 45 , 68 , 77 , 83 ]. For some, it also offered the potential for choice and the opportunity to plan when complications were detected [ 22 , 68 , 84 , 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the [25] recommendations for reducing perinatal mortalities, Zambia faces a signi cant challenge in effectively preventing and managing preterm birth and stillbirths due to the lack of an accurate, consistently applied estimated date of delivery (EDD) for each pregnant woman, which is obtained through ultrasound scanning. Studies from LMICs show that USS interventions delivered by midwives are highly feasible and acceptable [29,36,37]. Despite these ndings, there are still no known studies describing how ultrasound scanning is used in Zambia to decrease preterm and stillbirths.…”
Section: Introductionmentioning
confidence: 99%